PENGARUH GOOD CORPORATE GOVERNANCE DAN TAX AGGRESSIVENESS TERHADAP EARNINGS MANAGEMENT - Nur Azizah , Dienda; Indrastuti, Dewi Kurnia (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
The purpose of this study was to obtain empirical evidence regarding the effect of audit quality, board of commissioners, audit committee, institutional ownership, managerial ownership, firm size, leverage, and tax aggressiveness on earnings management which are the dependent variables. The population used in this study are non-financial companies listed on the Indonesia Stock Exchange (IDX) with a research period from 2019 to 2021. This study used a purposive sampling method to obtain data, as many as 98 companies that match the criteria used as a sample from this study. Discretionary accruals in this study were measured using the modified Jones model and the test method used to test the hypothesis in this study is the multiple regression analysis. The results of this study indicate that the variables of audit quality, board of commissioners, audit committee, institutional ownership, managerial ownership, firm size, leverage, and tax aggressiveness do not affect earnings management.